2002
DOI: 10.1091/mbc.e02-02-0087
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair and Transcriptional Effects of Mutations in TFIIH inDrosophilaDevelopment

Abstract: Mutations in XPB and XPD TFIIH helicases have been related with three hereditary human disorders: xeroderma pigmentosum, Cockayne syndrome, and trichothiodystrophy. The dual role of TFIIH in DNA repair and transcription makes it difficult to discern which of the mutant TFIIH phenotypes is due to defects in any of these different processes. We used haywire (hay), the Drosophila XPB homolog, to dissect this problem. Our results show that when hay dosage is affected, the fly shows defects in structures that requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 55 publications
(63 reference statements)
3
47
0
Order By: Relevance
“…Moreover, E2F and Dp53 are involved in inducing apoptosis in an independent manner during development, but both are required for apoptosis when DNA is damaged (Moon et al, 2008). However, in previous works, it has been reported that the apoptosis that is generated by the overexpression of p53 requires the presence of a functional TFIIH (Robles et al, 1999;Merino et al, 2002). In this study, we found that when both TFIIH and Dp53 were not functional in the wing imaginal disc, apoptosis was dramatically enhanced.…”
Section: Dp53 Physically Interacts With the Dmp52 Subunit Of Tfiihmentioning
confidence: 53%
See 2 more Smart Citations
“…Moreover, E2F and Dp53 are involved in inducing apoptosis in an independent manner during development, but both are required for apoptosis when DNA is damaged (Moon et al, 2008). However, in previous works, it has been reported that the apoptosis that is generated by the overexpression of p53 requires the presence of a functional TFIIH (Robles et al, 1999;Merino et al, 2002). In this study, we found that when both TFIIH and Dp53 were not functional in the wing imaginal disc, apoptosis was dramatically enhanced.…”
Section: Dp53 Physically Interacts With the Dmp52 Subunit Of Tfiihmentioning
confidence: 53%
“…Genetic interactions between TFIIH and p53 have been demonstrated in human cells derived from patients afflicted with xeroderma pigmentosum who carry mutations in XPD and XPB as well as in Drosophila XPB mutants (Robles et al, 1999;Wang et al, 2003;Merino et al, 2002). These studies were performed by overexpressing p53 to induce apoptosis in backgrounds deficient for XPD or XPB.…”
Section: Dp53 Physically Interacts With the Dmp52 Subunit Of Tfiihmentioning
confidence: 99%
See 1 more Smart Citation
“…TTDA is required for the stability of the TFIIH complex, but unlike XPB and XPD, which are implicated in all three diseases, defects in TTDA only cause the developmental disease TTD, not XP/CS and/or cancer 8,41 . Intriguingly, three different XPB families with mutations in ERCC3, the gene coding XPB, causing loss of the wild-type C terminus of XPB, all display the severe neurodegenerative progeroid disorder characteristic of CS, but have different cancer predisposition (one severe, one moderate, one with no cancer) 3,41,42 . Altogether with the knowledge that all patients in these families have reduced NER, these observations suggest that cancer phenotypes are not due to NER defects per se, but likely due to a second mutation.…”
mentioning
confidence: 99%
“…Haywire (Hay) is the Drosophila XPB homologue 40,41,43,44 , and loss-of-function Hay mutants display increased cell death, consistent with DNA repair and/or transcription defects 41,42,46 . The Drosophila orthologue of FIR, Half Pint (Hfp) behaves as a tumour suppressor, as loss of Hfp results in larval overgrowth and overproliferation 43,44 .…”
mentioning
confidence: 99%